Glacial geomorphology of the Skálafellsjökull foreland, Iceland : a case study of ‘annual’ moraines. - Chandler, B.M.P.; Evans, D.J.A.; Roberts, D.H.; Ewertowski, M.; Clayton, A.I. (Journal of Maps, 2016)
Small-scale recessional push moraines are a characteristic signature of the active temperate glacial landsystem, and are often clearly linked to annual re-advances. These recessional push moraines represent a potentially valuable terrestrial climate archive, and may provide valuable insights into glacier dynamics. This paper presents detailed glacial geomorphological maps of recessional push moraines on the foreland of Skálafellsjökull, SE Iceland. Geomorphological maps have been produced at a scale of 1:3750 based on 2006 aerial photographs and 2012 satellite imagery. Using unmanned aerial vehicle-captured imagery, large-scale sample mapping of two selected areas of the glacier foreland has also been conducted, with the maps reproduced as A4-sized figures at scales of ∼1:2500 and ∼1:2000, respectively. Desk- and field-based mapping reveals suites of recessional push moraines distributed across the glacier foreland, often found in close association with flutings. Moraines on the foreland typically display distinctive ‘sawtooth' planform geometries, with complexities in the pattern occurring due to localised superimposition. The inventory of glacial geomorphological maps presented here provides a framework for subsequently exploring the characteristics of the recessional push moraines and recent ice-marginal fluctuations at Skálafellsjökull.